The relationship between galectin-3 and SYNTAX Score I in patients with non-ST-segment elevation myocardial infarction - Alaa Quisi; Gökhan Alıcı; Ömer Genç; Hazar Harbalıoğlu; İbrahim Halil Kurt (KARE Publishing, 2020)
Objective: The expression of galectin-3 has been found to be increased in human atherosclerotic lesions, suggesting a role in atherogenesis. However, there is a lack of data regarding an association between galectin-3 and the extent, severity, and complexity of coronary artery disease (CAD). The aim of this study was to investigate the relationship between galectin-3 and SYNTAX Score I in patients with non-ST-segment elevation myocardial infarction (NSTEMI). Methods: This study included a total of 95 consecutive patients who were diagnosed with NSTEMI and underwent coronary angiography. The baseline galectin-3 level of each patient was measured. The SYNTAX Score I of each patient was calculated using the online calculator (www.syntaxscore.com). The study population was divided into 2 groups: SYNTAX Score I ≤22 group (n=55) and SYNTAX Score I >22 group (n=40). Results: The galectin-3 level was significantly higher in the SYNTAX Score I >22 group than in the SYNTAX Score I ≤22 group (22.1+-8.3 ng/mL vs. 13.5+-7.7 ng/mL; p<0.001). Forward stepwise logistic regression analysis demonstrated that galectin-3 (odds ratio [OR]: 1.195, 95% confidence interval [CI]: 1.097-1.302; p<0.001), left ventricular ejection fraction (OR: 0.941, 95% CI: 0.888-0.997; p=0.040), and platelet count (OR: 1.013, 95% CI: 1.003-1.024; p=0.014) were independently associated with intermediate and high SYNTAX scores. ROC analysis provided a cut-off value of 14.0 ng/mL for galectin-3 to predict an intermediate or high SYNTAX Score I with 75.0% sensitivity and 51.0% specificity (p<0.001). Conclusion: In patients with NSTEMI, galectin-3 was associated with the extent, severity, and complexity of CAD as assessed by the SYNTAX Score I.